FAUNA NYAMUK ANOPHELES DI DESA LEMAHJAYA, KECAMATAN WANADADI, KABUPATEN BANJARNEGARA, TAHUN 2011 - Anggun Paramita Djati; Dwi Priyanto; Hari Ismanto; Adil Ustiawan (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Malaria is still a health problem in Banjarnegara District. Efforts to prevent and control malaria requires basic information on vector surveillance data, including the species, and breeding place. This study obtain a suspected vector information, focus on Anopheles in Lemahjaya, where is an increase of malaria cases. Data collected by entomological survey and survey of malaria mosquito breeding place. Result of mosquito collection found above mentioned various means 7 species of Anopheles that is An.aconitus (12,15%), An.maculatus (61,68%), An.balabacensis (1,87%), An.vagus ( 10,28%), An.kochi ( 6,54%), An.barbirostris ( 6,54%), dan An.tessellatus (0,93%). From seventh of the species is confirmed as vector of malaria is An.aconitus and An.maculatus. An.aconitus Predominantly species is An. maculatus. The biting and resting behaviour of An.maculatus found all night, since evening and the peak density at 21.00 until 22.00, 03.00 until 04.00 in outdoor and 24.00 – 01.00 in cattle. Result of entomological survey related to people's behavior which have outdoor activity at night and result of malaria mosquito breeding place found An. maculatus larvaes.